Influence of Transformational Leadership on Job Performance: Employee Work Engagement as Test Mediation - Sarfilianty Anggiani (Indonesian Management and Accounting Research, 2021)
The study aims at investigating of this study is to examine how the effect of transformational leadership on job performance by mediating employee work engagement on employees of the Human Capital and Facility Management division of PT. XL Axiata, Tbk. Jakarta. The data were collected from 58 employees Facility division of Human Capital Management PT. XL Axiata Tbk. Jakarta. For the serial analysis, SPSS macro process was utilized to test the proposed hypothesis model. Results provide evidence that follower employee work engagement mediates the relationship between perceived transformational leadership and job performance. By better understanding how leaders build engagement and drive performance in regard to a specific task, organizations can take advantage of the influence that leaders have on everyday interactions in workplace. Therefore, in this study more developed the psychological profile of effective leaders, especially the communications industry, management researchers must explore work involvement and people's orientation.